PENERAPAN MODELPEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VSDN4 SUNGAI SIPUT KECAMATAN SIAK KECILKABUPATEN BENGKALIS - Irma Yuniati; Zariul Antosa; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abtract : The research was conducted with the aim to improve learning outcomes fifth grade science students SDN 4 River Snail Bengkalis District of Siak Kecil. The school year 2014/2015. IPA learning outcome can be viewed through the "Implementation of Cooperative Learning Model Two Stay Two Stray" The research was conducted in March and April 2015 the number of male students 12 and 8 female students. This research was conducted in two Siklus.instrument used in this activity is a learning device that consists of a syllabus, lesson plans, and Lks. Collecting data using test equipment in the form of observation sheet and test results of learning. The following data will be analyzed in this study. Student activity data is increasing at silkus II with a score of 83.33 with very good category. Student learning outcomes data also increased from the base score. Daily test I and replicates Daily II saw an increase, on the basis of the average scores obtained by students was 55.25 while the KKM that has been set is 6.5. In the daily tests first cycle an increase in the average value to 67.5. Then daily tests second cycle back an increase in the average value of 82.25. From the research that the implementation of cooperative learning model two stay two stray can improve learning outcomes Students IPA kelasV SDN 4 Sungai Siput, Kecamatan Siak Kecil, Kabupaten BengkalisKeywords : Cooperative Learning Model Application of two types Stay two stray, Science Learning Outcomes, and PTK.